Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1038/ncb1404
|View full text |Cite|
|
Sign up to set email alerts
|

APPL1 binds to adiponectin receptors and mediates adiponectin signalling and function

Abstract: Adiponectin, also known as Acrp30, is an adipose tissue-derived hormone with anti-atherogenic, anti-diabetic and insulin sensitizing properties. Two seven-transmembrane domain-containing proteins, AdipoR1 and AdipoR2, have recently been identified as adiponectin receptors, yet signalling events downstream of these receptors remain poorly defined. By using the cytoplasmic domain of AdipoR1 as bait, we screened a yeast two-hybrid cDNA library derived from human fetal brain. This screening led to the identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
672
2
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 594 publications
(722 citation statements)
references
References 27 publications
31
672
2
11
Order By: Relevance
“…Indeed, it has been shown that the insulin signaling pathway is regulated by various feedback mechanisms. For instance, plasma insulin is upregulated in response to downregulation of insulin receptor signaling, resulting in insulin resistance,46 and APPL1, an adaptor protein containing a PH domain, PTB domain, and leucine zipper motif,47 has been increased in AD, perhaps in response to impaired insulin receptor signaling 48…”
Section: Apn May Promote Neurodegeneration In Ad Through Novel Mechanmentioning
confidence: 99%
“…Indeed, it has been shown that the insulin signaling pathway is regulated by various feedback mechanisms. For instance, plasma insulin is upregulated in response to downregulation of insulin receptor signaling, resulting in insulin resistance,46 and APPL1, an adaptor protein containing a PH domain, PTB domain, and leucine zipper motif,47 has been increased in AD, perhaps in response to impaired insulin receptor signaling 48…”
Section: Apn May Promote Neurodegeneration In Ad Through Novel Mechanmentioning
confidence: 99%
“…27 These receptors are biologically active, as they bind to a protein known as adaptor protein-containing pleckstrin homology domain, phosphotyrosine-binding domain and leucine zipper motif (APPL1), and provoke intracellular signaling. 28,29 Circulating adiponectin concentrations correlate negatively with body fat in mammals. 30 The concentration of adiponectin in circulation can exceed 10 mg ml À1 in humans and is inversely related to adipose mass.…”
Section: Adiponectin: Structure and Functionmentioning
confidence: 99%
“…34 There is evidence for adiponectin activation of the peripheral peroxisome-activated receptor-g in placental tissue 57 and mitogen-activated protein kinase pathways in vascular tissue 70,71 and osteoblasts. 72 The recent discovery of interactions between the AdipoR1 and R2 and the adapter protein APPL1 28,29 has provided new insight into the mechanism by which adiponectin can act on target tissues. APPL1 has been implicated in the regulation of cross-talk between the insulin and adiponectin transduction pathways.…”
Section: Mechanisms Of Action Of Adiponectin In Reproductive Tissuesmentioning
confidence: 99%
See 2 more Smart Citations